Legal Protection for Minority Shareholders Arising from the Delisting of Issuer Shares (A Comparative Study of Indonesian, United States, and Singapore Law) - Hilda Kurnia Ningsih; Richard C. Adam (Universitas Trunodjoyo Madura, 2023)
This research paper provides a comparative analysis of the legal frameworks governing the delisting of issuer shares in Indonesia, the United States, and Singapore. Using a normative legal research approach, supplemented by interviews with members of the Financial Services Authority (OJK) and a Member of the House of Representatives Commission XI, the study explores how each jurisdiction addresses the delisting process, particularly focusing on the protection of minority shareholders . The analysis reveals that Indonesia's legal system, influenced by its Civil Law heritage, contrasts with the Common Law approaches of the US and Singapore, especially in terms of shareholder involvement in voluntary delisting and the specificity of conditions for forced delisting. The study suggests enhancements to the Indonesian framework, such as clearer guidelines for shareholder approval in delisting decisions and more transparent criteria for forced delisting. These recommendations aim to improve the protection of minority shareholders within Indonesia's Capital Market.